KEPEMILIKAN RAHASIA DAGANG FORMULA CAT RAMBUT: Ownership Of Hair Dye Formula Trade Secret - Viranda Mirella; Rr. Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2026)
Trade secrets constitute assets of significant economic value requiring comprehensive legal protection, particularly within the salon industry where hair dye formulas serve as a primary competitive advantage. The problem regarding the entitlement to ownership of hair dye formula trade secrets within a salon based on Law Number 30 of 2000 concerning Trade Secrets. The research methodology employed is normative legal research, utilizing both a statutory approach and a conceptual approach. Primary legal materials include Law Number 30 of 2000 concerning Trade Secrets, whereas secondary legal materials; treatises pertaining to intellectual property rights. The result of this research indicate that Law Number 30 of 2000 concerning Trade Secrets lacks specific provisions governing the ownership of trade secrets arising from an employment relationship, as otherwise regulated under copyright and patent regimes. However, it can be concluded that in the event a hair dye formula is conceived by a stylist without the utilization of salon facilities, the trade secret shall vest in the stylist. Consequently, the ownership of hair dye formula trade secrets in salons is determined by several legal criteria, inter alia: the creator of  formula, the existence of an employment or licensing agreement, and security measures implemented by proprietor of information